Pentahelix Movement Through Ecopreneurship-based Waste Management - Muyassarah Muyassarah; Muhammad Saiful Muslim; Fita Nurotul Faizah; Ahmad Tajuddin Arafat (LP2M of Institute for Research and Community Services - UIN Walisongo, 2022)
Waste is a major problem in environmental management. This is due to the low level of public awareness and lifestyle toward waste management. This service aims to foster and increase public awareness of waste management and increase community ecopreneurship through training in making Eco-Enzyme in Langenharjo Village, Kendal. To achieve these goals, the UIN Walisongo community service team formed a Pentahelix movement by collaborating with the Kendal Regency Government Environment Office, Bank Sampah Induk (BSI) Kendal, Kendal Family Welfare Development Team (PKK), Kendal Industrial Estate (KIK) and Kendal Regency National Narcotics Agency (BNN). The implementation method uses the Participatory Action Research (PAR) method which includes three stages, preparation, implementation, and evaluation of activities. The number of training participants was 80 participants. The results of the service showed that the socialization and training of eco-enzyme were able to foster and increase public awareness by 80% with 65% from parents and the rest from millennials. This means that this socialization is quite effective and can really impact the surrounding community towards waste reduction. Meanwhile, the ecopreneurship training by turning waste into Eco-Enzyme was able to be followed by all participants, because the manufacturing process was quite easy. Unfortunately, the participation of participants from the millennial generation was still passive when compared to the enthusiasm of participants from the parent group. Nevertheless, this activity can be the first step in fostering the entrepreneurial spirit of the Langenharjo Kendal community through waste ecopreneurship.